2016
DOI: 10.1095/biolreprod.115.135780
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia As Modulator of Offspring Health1

Abstract: A balanced intrauterine homeostasis during pregnancy is crucial for optimal growth and development of the fetus. The intrauterine environment is extremely vulnerable to multisystem pregnancy disorders such as preeclampsia, which can be triggered by various pathophysiological factors, such as angiogenic imbalance, immune responses, and inflammation. The fetus adapts to these conditions by a mechanism known as developmental programming that can lead to increased risk of chronic noncommunicable diseases in later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 127 publications
0
42
0
9
Order By: Relevance
“…Several previous studies have shown that low birth weight increases the risk of cardiovascular and metabolic diseases, for example, stroke, diabetes, obesity, etc. [23][24][25][26][27] Potential factors include malnutrition and toxins present during pregnancy. Our data demonstrate that fetal exposure to sFlt-1 is associated with asymmetrical growth restriction, however to what extent this contributes to developmental programming of the fetus still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that low birth weight increases the risk of cardiovascular and metabolic diseases, for example, stroke, diabetes, obesity, etc. [23][24][25][26][27] Potential factors include malnutrition and toxins present during pregnancy. Our data demonstrate that fetal exposure to sFlt-1 is associated with asymmetrical growth restriction, however to what extent this contributes to developmental programming of the fetus still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the long-term, stroke risk at Age 65 appears elevated, though coronary artery disease was not increased [98]. Metabolic consequences such as obesity, insulin resistance and increased vascular inflammatory markers have also been noted at younger ages and animal studies suggest possible causal links [99].…”
Section: Preeclampsia and Later Infant Healthmentioning
confidence: 99%
“…Although PE is a multifactorial disorder, several pathophysiological mechanisms including angiogenic imbalance, excessive inflammation, ischaemia/perfusion and imbalances in the renin angiotensin system are all implicated in its pathogenesis. 22,23 During a pregnancy complicated by PE, the placenta releases circulating factors, including sFlt and sEng, 24,25 into the maternal circulation as a result of syncytiotrophoblast stress due to a variety of insults including placental ischemia/hypoxia, contributing to excessive inflammation and generation of reactive oxygen species. [26][27][28][29] Consistent with a causal role for these placental factors in programming of progeny CVD, overexpression of sFlt in a mouse model of PE mimicking the placenta of a pregnancy affected by PE results in elevated systolic and diastolic blood pressure in male offspring.…”
Section: Developmental Programming Of Cvd Risk By In Utero Exposure Tmentioning
confidence: 99%